(untitled) (Revista INTEREDU11, 2024)
Interventions in School Mental Health (SME) have gained greater prominence in the last decade through the Life Skills Program (HPV); however, it’s pointed out that a hindering factor of these is the management of educational establishments, mainly because of the recourse of time. The study aims to investigate the social representations of members of management teams of educational establishments attached to the HPV Program of the University of La Frontera, through two main concepts: school mental health and school mental health management. A participatory action research methodology was adapted with focus group techniques and natural semantic networks, examining the data through content analysis. The participants represented EMS as wellbeing, in addition, it is observed that they have an understanding that EMS management has different levels of realization and that it requires the participation of the entire educational community.